INTERPRETTING INTERCULTURAL COMMUNICATION APPROACH OF INDONESIAN DIASPORA IN TURKIYE - Muhammad Danu Winata; Jauhar Wahyuni; Tatak Setiadi; Gilang Gusti Aji; Ilyas Akhisar (Profetik: Jurnal Komunikasi, 2023)
The understanding of the importance of intercultural communication carried out by the Indonesian Diaspora in Turkiye can provide an accurate picture of the actual conditions of the processes that occur in intercultural communication between Indonesian culture and Turkish culture. Qualitative descriptive research in this research was carried out with in-depth interviews with three respondents who were in Turkiye. Each represented the Indonesian diaspora in the scope of Government, namely the Cultural Attaché of the Republic of Indonesia, then the Indonesian Student Association in Turkiye, and Indonesian workers who were active in Turkiye. Research reveals that the pattern of the Indonesian diaspora in conducting intercultural communication is by understanding each other between two or more cultures and establishing close relationships in the work environment, study environment, to the social and Government environment, including an approach with adaptability to socializing styles, culinary, to the artistic attractions of each culture. With this understanding and adaptation attitude, it turns out that the Indonesian diaspora also opens up opportunities to become bridging agents in the exchange of two cultures, Indonesia and Turkiye, and shows the occurrence of a two-way intercultural communication process.